BIO-ECOLOGICAL STUDY OF MYZUS PERSICAE (HOMOPTERA, APHIDIDAE) AT EL-OUED REGION, ALGERIA - A, Haddad*1; A, Zaater1; A., Ladjali1 and; A., Djerah2 (university of eloued جامعة الوادي, 2019)
The region of El-Oued in the south-east of Algeria is arid. A pole of production of greenhouse vegetable crops that are threatened by the green peach aphid (Myzus persicae) that causes damage of up to 35% of the tomato and pepper crop. A study was conducted in 4 Stations, that of S'till, Djamaa, El-Magran and Oued El-Alenda, during the campaigns 2017 and 2018. The results obtained showed that the averages of the numbers of Myzus persicae highest are mentioned in March with 28.48 ± 0.14 individuals on the mercedes variety and 33.99 ± 0.12 individuals on the wided variety and 32.24 ± 0.22 individuals on the sultan variety of pepper. However, the average of the lowest numbers is 1.62 ± 0.03 wided on 0.98 ± 0.07 individuals on Mercedes, recorded during mid-January and 0.72 ± 0.03 aphids on pepper, variety Sultan, on the same date.
artical
Keywords: green aphid; tomato; pepper; bioecology; greenhouse.